2009
DOI: 10.1371/journal.pone.0008152
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Human iPS-Derived Retinal Pigment Epithelium Cell Transplantation in the Retinal Dystrophic Rat

Abstract: Transformation of somatic cells with a set of embryonic transcription factors produces cells with the pluripotent properties of embryonic stem cells (ESCs). These induced pluripotent stem (iPS) cells have the potential to differentiate into any cell type, making them a potential source from which to produce cells as a therapeutic platform for the treatment of a wide range of diseases. In many forms of human retinal disease, including age-related macular degeneration (AMD), the underlying pathogenesis resides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
372
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(399 citation statements)
references
References 72 publications
12
372
0
8
Order By: Relevance
“…Expression of Visual Cycle Molecules in RPE Cells-Differentiation of RPE cells from ES and iPS cells has been reported (8,9), and some RPE functions have been characterized in these cells. These include the expression of RPE-specific molecules such as BEST1, MERTK, RPE65, and CRALBP along with the capability to carry out phagocytosis, form adherence junctions, and produce cytokines (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Visual Cycle Molecules in RPE Cells-Differentiation of RPE cells from ES and iPS cells has been reported (8,9), and some RPE functions have been characterized in these cells. These include the expression of RPE-specific molecules such as BEST1, MERTK, RPE65, and CRALBP along with the capability to carry out phagocytosis, form adherence junctions, and produce cytokines (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups have reported that human ES and iPS cells can be differentiated into RPE cells which display some degree of RPE functionality, including phagocytosis and growth factor secretion (8,9). However, the visual (retinoid) cycle in hiPS-derived RPE (hiPS-RPE) cells has not been rigorously examined.…”
Section: Moreover Histological Analyses Of These Eyes Displayed Replmentioning
confidence: 99%
“…Although the process for deriving pure populations of retinal precursors from iPSCs is less efficient than for ESCs, culture protocols to differentiate iPSC-RSCs into photoreceptor cell precursors are sufficiently developed so that such progeny integrate into mouse retina and differentiate into both rod and cone photoreceptor cells [71]. Transplantation of iPSCs differentiated into functional iPS-RPE into the RCS rat retina resulted in the maintenance of longterm visual function, even after the xenografted cells were eventually lost to immune rejection, raising the possibility that a secondary protective host cellular response rescued photoreceptor cells [73]. iPSC are a promising source for retinal replacement therapy, although with significant remaining challenges to their clinical use.…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…Production of RPE cells from ESC and iPSC has been established by a number of different laboratories that have developed protocols for generation of homogeneous polarized RPE monolayer cultures. 12,45,46,47 iPSC-derived RPE cells can be isolated, expanded, differentiated, reseeded, and monitored both for morphology and functionality. 48 Also highly significant has been the discovery that iPSC/ ESC are able to self-assemble into three-dimensional (3D) optic cup structures, which then form stratified neural retinal tissues.…”
Section: Retinal Differentiation Of Ipscmentioning
confidence: 99%